2013
DOI: 10.2459/jcm.0b013e328356a4e6
|View full text |Cite
|
Sign up to set email alerts
|

Nonfluoroscopic mapping reduces radiation exposure in ablation of atrial fibrillation

Abstract: A fast nonfluoroscopic electroanatomical mapping system may reduce radiation exposure in RFCA of atrial fibrillation, with preserved success rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Simplification of the ablation procedure by single shot ablation systems such as the CB and CB2 has further contributed to PVI popularity, because CB has shortened procedure times and learning curves, and shown non‐inferiority regarding safety and freedom from AF as compared to point‐by‐point RF ablation 2–4,14 . On the other hand, when compared with conventional RF ablation, CB PVI is associated with a prolonged fluoroscopy time/higher radiation exposure, since CB PVI is fluoroscopy guided while RF‐ablation is typically supported by 3D electroanatomical mapping 3–6 . Modifications of radiation modalities by reducing fluoroscopy frame rates, optimizing collimation, omitting cine runs together with selective PV angiographies, and preferring fluoroscopic pa projections, whenever possible can significantly reduce radiation exposure, as shown in our study and demonstrated by others recently 8–10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simplification of the ablation procedure by single shot ablation systems such as the CB and CB2 has further contributed to PVI popularity, because CB has shortened procedure times and learning curves, and shown non‐inferiority regarding safety and freedom from AF as compared to point‐by‐point RF ablation 2–4,14 . On the other hand, when compared with conventional RF ablation, CB PVI is associated with a prolonged fluoroscopy time/higher radiation exposure, since CB PVI is fluoroscopy guided while RF‐ablation is typically supported by 3D electroanatomical mapping 3–6 . Modifications of radiation modalities by reducing fluoroscopy frame rates, optimizing collimation, omitting cine runs together with selective PV angiographies, and preferring fluoroscopic pa projections, whenever possible can significantly reduce radiation exposure, as shown in our study and demonstrated by others recently 8–10 …”
Section: Discussionmentioning
confidence: 99%
“…In a recently published meta‐analysis, CB PVI was noninferior to RF PVI with respect to safety and efficacy 2 . However, CB PVI is generally associated with an increased radiation exposure compared to RF ablation where catheter guidance can be achieved with three‐dimensional (3D) mapping 3–6 …”
Section: Introductionmentioning
confidence: 99%
“…Compared with some other studies, our studies seems to provide a lower dose of radiation exposure in DAP and AK. [ 5 7 8 ]…”
Section: R Esultsmentioning
confidence: 99%
“…[ 1 2 3 4 ] Radiation exposure can only be reduced but cannot be avoided although the use of three-dimensional electroanatomical (EAM) mapping systems. [ 5 6 ] It is a challenge for the operator to reduce the radiation dose as far as possible.…”
Section: Introductionmentioning
confidence: 99%